2016
DOI: 10.1007/s00705-016-2960-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection in blood donors in Argentina: prevalence of infection, genotype distribution and frequency of occult HBV infection

Abstract: This study describes the prevalence of HBV infection based on detection of HBsAg and HBV-DNA by NAT in 70,102 blood donors in Argentina (Córdoba province) and shows the viral genotype distribution and frequency of occult HBV infection (OBI) in this population. Forty-two donors were confirmed positive for HBV infection (0.06 %), and four had OBI. Genotype F was the most prevalent (71.4 %), followed by A (14.3 %), C (7.1 %) and D (7.1 %). This is the first report of the prevalence of confirmed HBV infection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In a recent publication of our group, an OBI prevalence of one in 17,525 (4/70,102) based on virologic and serologic profiles at time of donation was reported for some donors that are included in this study. Complementary serologic assays and follow‐up performed of donors with suspected OBI allowed us a better characterization of these infections and to define a rate of OBIs detected by NAT in a larger casuistry as 1.8 in 100,000 donors (3/168,215).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication of our group, an OBI prevalence of one in 17,525 (4/70,102) based on virologic and serologic profiles at time of donation was reported for some donors that are included in this study. Complementary serologic assays and follow‐up performed of donors with suspected OBI allowed us a better characterization of these infections and to define a rate of OBIs detected by NAT in a larger casuistry as 1.8 in 100,000 donors (3/168,215).…”
Section: Discussionmentioning
confidence: 99%
“…However, the data on the study of blood donors, stem cells, and organs for the presence of OHB are little and contradictory. For example, among blood donors in Argentina (n = 70 102), HBV was detected in only 0.06% of the samples, of which only four were OHB [35]. In the Lao People's Democratic Republic, the prevalence of OHB among HBsAg-negative blood donors was 10.9% [23].…”
Section: Resultsmentioning
confidence: 98%
“…In the Lao People's Democratic Republic, the prevalence of OHB among HBsAg-negative blood donors was 10.9% [23]. In Nigeria, the incidence of OHB among blood donors reached 17% [35]. In the analysis of healthy stem cell donors from South Korea, OHB was detected in 15.3%, which, like in the case of a significant occurrence of OHB in the population, can be explained by the high prevalence of hepatotropic viruses in this geographic region [20].…”
Section: Resultsmentioning
confidence: 99%
“…The "anti-HBc" serological status could be attributed to different parameters among which are: (a) passive transfer of anti-HBc; (b) a recent HBV infection during which HBsAg has disappeared, while anti-HBs levels are yet undetectable; or (c) chronic HBV infection during which HBsAg is undetectable due to very low viraemia, a clinical phase recognized as occult HBV infection (14)(15)(16)(17). Although many countries implement an anti-HBc test before blood transfusion, in an attempt to decrease the risk of HBV transmission, recent studies (18)(19)(20) clearly demonstrated an absence of correlation between anti-HBc positivity and presence of HBV-DNA, indicating that anti-HBc screening is not a recommended method to identify HBV infection. For instance, a donor showing positivity for anti-HBc may be a naïve-HBV carrier i.e.…”
Section: Discussionmentioning
confidence: 99%